A Ru / NiFe-LDH composite material and its preparation method and application in activating PMS to degrade organic matter in water
By using Ru/NiFe-LDH composite material as a catalyst, PMS is activated to degrade organic matter, solving the problem of low activation efficiency in the prior art, and achieving efficient degradation of organic matter in wastewater.
Patent Information
- Application Number
- CN202410526492.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-29
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2044-04-29
AI Technical Summary
The existing PMS activation methods have the problem of low activation efficiency, and it is difficult to achieve efficient degradation of organic matter in wastewater.
Ru/NiFe-LDH composite material was used as a catalyst and prepared by simple hydrothermal reaction and ultrasonic mixing methods to activate PMS to degrade organic matter.
Ru/NiFe-LDH composites have high catalytic properties, a wide pH range, strong anti-anionic interference ability, and can efficiently degrade organic matter in water.
Smart Images

Figure CN118527155B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of nanocatalysis and organic wastewater treatment, and in particular to a Ru / NiFe-LDH composite material and a preparation method thereof, and application thereof in activating PMS to degrade organic matter in water. Background Art
[0002] In recent years, advanced oxidation technology based on permonosulfate (PMS) has shown great potential in the treatment of organic wastewater due to its simple operation and ability to produce highly oxidative reactive oxygen radicals (ROS). However, existing PMS activation methods, such as ultraviolet activation, thermal activation, and transition metal activation, have the problem of low activation efficiency. Therefore, it is urgent to find a new catalyst with high catalytic activity and wide pH range adaptability and its preparation method, which is of great significance for achieving efficient degradation of organic matter in wastewater.
[0003] Based on this, the present invention proposes a Ru / NiFe-LDH composite material that can be used to activate PMS to degrade organic matter and a preparation method thereof. Summary of the invention
[0004] In view of the technical problems existing in the prior art, the present invention provides a Ru / NiFe-LDH composite material and a preparation method thereof and application thereof in activating PMS to degrade organic matter in water. The Ru / NiFe-LDH composite material is prepared by a simple method and has good catalytic performance.
[0005] The technical solution of the present invention is as follows:
[0006] A method for preparing a Ru / NiFe-LDH composite material comprises the following steps:
[0007] S1, uniformly mixing nickel salt, iron salt, urea, ammonium fluoride and water by ultrasonication, performing hydrothermal reaction, filtering, drying and grinding to obtain NiFe-LDH powder;
[0008] S2. Dissolve RuCl3 in a beaker containing 85 ml ultrapure water and 10 ml 0.1 M NaOH; then add NiFe-LDH powder and stir at 50-60°C for 6-8 hours to obtain a dark green sample, which is then washed thoroughly with deionized water and dried.
[0009] Among them, the mass ratio of RuCl3 to NiFe-LDH powder is 15~20:400~500.
[0010] Furthermore, the ratio of the nickel salt, the iron salt, the urea, the ammonium fluoride and the water is 3-4 mmol: 1-1.5 mmol: 120-130 mmol: 10-15 mmol: 80-90 ml.
[0011] Furthermore, the ratio of the nickel salt, the iron salt, the urea, the ammonium fluoride and the water is 3mmol:1mmol:120mmol:10mmol:80ml.
[0012] Furthermore, the ultrasonic time is 15-25 min.
[0013] Furthermore, the hydrothermal reaction temperature is 110-120° C. and the time is 10-12 hours.
[0014] A Ru / NiFe-LDH composite material prepared by the above preparation method.
[0015] An application of the above-mentioned Ru / NiFe-LDH composite material in activating PMS to degrade organic matter in water.
[0016] Furthermore, the amount of the Ru / NiFe-LDH composite material used in the degradation process is 0.18-0.2 g / L.
[0017] Furthermore, the initial pH of the degradation process is 3-11.
[0018] Furthermore, the method further comprises: depositing the Ru / NiFe-LDH composite material on the PES membrane.
[0019] Compared with the prior art, the present invention has the following beneficial effects:
[0020] The invention provides a simple preparation method of a Ru / NiFe-LDH composite material, and proposes that the Ru / NiFe-LDH composite material can be used as a catalyst for activating PMS to degrade organic matter in wastewater. The composite material has high degradation efficiency, a wide applicable pH range, and strong anti-anion interference ability. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0022] Figure 1 SEM, TEM and EDS spectra of Ru / NiFe-LDH;
[0023] Wherein, a represents the preparation process of Ru / NiFe-LDH; bc represents the SEM of Ru / NiFe-LDH, de represents the HAADF-STEM image of Ru / NiFe-LDH at low resolution, and fj represents the HAADF-STEM image of Ru / NiFe-LDH at high resolution and the corresponding EDS spectrum;
[0024] Figure 2 XRD patterns of Ru / NiFe-LDH and NiFe-LDH;
[0025] Figure 3 is the Fourier transform infrared (FT-IR) spectrum of Ru / NiFe-LDH composite;
[0026] Figure 4 is the XPS spectrum of Ru / NiFe-LDH;
[0027] Among them, a is the full XPS spectrum of Ru / NiFe-LDH and NiFe-LDH, b is the high-resolution XPS spectrum of Fe, and c is the high-resolution XPS spectrum of Ni;
[0028] Figure 5 The results of the study on the catalytic performance of Ru / NiFe-LDH in activating PMS to degrade SMX;
[0029] Among them, a is the degradation of SMX under different catalytic systems, b is the degradation of SMX under different Ru loading conditions, (c) the degradation of SMX with different PMS additions, (d) the degradation of SMX with different catalyst additions, (e) the degradation of SMX at different pH values, and (f) the degradation of SMX under different anion interferences. (In the figure, the initial conditions of the reaction are: [Ru / NiFe-LDH]=0.2g / L, [PMS]=0.5mM, T=25℃, pH=7.0, [SMX]=10mg / L);
[0030] Figure 6 The results of the study on the performance of Ru / NiFe-LDH in activating PMS to degrade organic matter;
[0031] Among them, a is the degradation efficiency in different water matrices, b is the degradation of each pollutant by the Ru / NiFe-LDH / PMS system, c is the degradation by adding different anions and organic matter, d is the continuous flow degradation device, e is the photo of the Ru / NiFe-LDH / PES catalytic membrane, f is the SEM image of the Ru / NiFe-LDH / PES catalytic membrane, g is the photo of the pure PES membrane, h is the SEM image of the pure PES membrane, i is the degradation of SMX in the Ru / NiFe-LDH / PES / PMS filtration system, and j is the water flux of the Ru / NiFe-LDH / PES catalytic membrane and the pure PES membrane. (Working conditions: [SMX]0=10mg / L, [PMS]0=0.5mM, pH07.0). DETAILED DESCRIPTION
[0032] In order to make the above-mentioned purposes, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the accompanying drawings. The following content is only an example and explanation of the concept of the present invention. The technicians in the relevant technical field make various modifications or supplements to the specific implementation cases described or replace them with similar methods. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.
[0033] Unless otherwise specified, the raw materials, equipment, etc. involved in the present invention are common commercially available products.
[0034] Embodiment 1: A method for preparing a Ru / NiFe-LDH composite material, comprising the following steps:
[0035] (1) Preparation of nickel-iron hydrotalcite (NiFe-LDH):
[0036] Dissolve 3.6mmol Ni(NO3)26H2O, 1.2mmol Fe(NO3)9H2O, 126mmol urea and 10mmol ammonium fluoride in 80ml ultrapure water. Ultrasonicate for 20min. Mix the materials thoroughly. Then place the mixed solution in a reactor and react in an oven at 110~120℃ for 10~12 hours. After obtaining the sample, filter and wash it. Then dry it in an oven at 50~60℃ for 24 hours and grind it into powder.
[0037] (2) Preparation of Ru / NiFe-LDH composite materials:
[0038] Dissolve 15 mg of RuCl3 in a beaker containing 85 ml of ultrapure water and 10 ml of 0.1 M NaOH. Add NiFe-LDH (0.4 g) and stir at 50-60 °C for 6-8 hours to obtain a dark green sample, which is then washed thoroughly with deionized water. Finally, dry it in a vacuum oven at 50-60 °C overnight, and determine the Ru content in Ru / NiFe-LDH by ICP-MS to be 1.5543 wt%, which is named Ru / NiFe-LDH.
[0039] Embodiment 2: A method for preparing a Ru / NiFe-LDH composite material, comprising the following steps:
[0040] (1) Preparation of nickel-iron hydrotalcite (NiFe-LDH):
[0041] Dissolve 3mmol of Ni(NO3)26H2O, 1mmol of Fe(NO3)9H2O, 126mmol of urea and 15mmol of ammonium fluoride in 90ml of ultrapure water. Ultrasonicate for 20min. Mix the materials thoroughly. Then place the mixed solution in a reactor and react in an oven at 120℃ for 10 hours. After obtaining the sample, filter and wash it. Then dry it in an oven at 50℃ for 24 hours and grind it into powder.
[0042] (2) Preparation of Ru / NiFe-LDH composite materials:
[0043] Dissolve 20 mg of RuCl3 in a beaker containing 90 ml of ultrapure water and 10 ml of 0.1 M NaOH. Add NiFe-LDH (0.5 g) and stir at 50 °C for 6 hours to obtain a dark green sample, which is then washed thoroughly with deionized water. Finally, dry in a vacuum oven at 50 °C overnight, and determine the Ru content in Ru / NiFe-LDH to be 1.6621 wt% using ICP-MS.
[0044] Comparative Example 1: Step (1) is the same as in Example 1;
[0045] (2) Preparation of Ru / NiFe-LDH composite materials:
[0046] Dissolve 10 mg of RuCl3 in a beaker containing 85 ml of ultrapure water and 10 ml of 0.1 M NaOH. Add NiFe-LDH (0.5 g) and stir at 50-60 °C for 6-8 hours to obtain a dark green sample, which is then washed thoroughly with deionized water. Finally, dry in a vacuum oven at 50-60 °C overnight, and determine the Ru content in Ru / NiFe-LDH by ICP-MS to be 0.839 wt%, named Ru / NiFe-LDH*.
[0047] Performance Testing
[0048] The degradation experiment was carried out in a 250.0mL conical flask, which was placed on a water bath shaker and oscillated at 150rpm. Taking SMX as an example of organic matter, the specific steps are as follows: a certain concentration of compound (SMX 10.0mg / L and catalyst 0.2g / L) was placed in a conical flask, and the pH value was adjusted with diluted H2SO4 and NaOH solution to form a 100.0ml reaction system (pH=7). Then, 0.5mM PMS was added to the conical flask to start the reaction at room temperature 25℃. During the entire reaction process, aliquots of samples were collected at regular intervals and filtered through a 0.22µm filter membrane, and then placed in an HPLC vial containing 20µl 0.33M sodium thiosulfate solution for immediate analysis. In addition, the degradation of SMX in water matrices and natural organic matter in the presence of various inorganic anions was studied. MeOH was selected to scavenge •OH, SO4•-, FFA to scavenge 1 O2, TBA to scavenge •OH, and DMSO to scavenge Ru(V)=O. PMSO was used to quantify the contribution of Ru(V)=O.
[0049] 1. Characterization of Catalyst
[0050] Images from a scanning electron microscope (SEM) ( Figure 1 ) shows that NiFe-LDH and Ru / / NiFe-LDH are composed of sheet-like nanoblocks forming a three-dimensional network structure. The average size is 10µm as determined by a laser particle size analyzer, which has sufficient specific surface area, indicating that hydrotalcite has enough sites to provide conditions for the loading of Ru. In addition, in the X-ray diffraction (XRD) diagram ( Figure 2 ), Ru / NiFe-LDH did not show any new peaks, and the original peak intensity did not change after loading, indicating that the loading of Ru did not affect the crystal structure of hydrotalcite. The Fourier transform infrared (FT-IR) spectrum of the synthesized LDH is shown in Figure 3 As shown in the figure, the peaks at 3440 cm-1 and 1649 cm-1 are attributed to the stretching and bending vibrations of OH- and H2O between the layers, respectively, and the peaks at 1357 cm-1 and 783 cm-1 represent the stretching and bending effects of CO32- anions. These evidences indicate that CO32- and water molecules exist between the NiFe-LDH layers, indicating that LDH was successfully synthesized and that the rich functional groups of LDH provide favorable conditions for loading Ru. Low-resolution STEM confirmed that no nanoparticles were formed on the surface of the material. Aberration-corrected high-angle annular dark field scanning TEM (HAADF-STEM) observed that Ru was atomically dispersed on NiFe-LDH. Figure 1The bright spot marked by the red circle in d is an isolated Ru atom, and the atomic-level dispersion of Ru on LDH is further confirmed by atomic-level resolution mapping.
[0051] 2. Electronic structure of catalyst
[0052] In order to further analyze the electronic environment of the coordination center, XPS analysis was performed on the two LDH samples before and after loading. The XPS of Ru / NiFe-LDH showed that ( Figure 4 a), the LDH is composed of Ru, Ni, Fe, C and O. The high-resolution XPS spectra of Ni2p and Fe 2p in all samples are divided into 2p1 / 2 and 2p3 / 2 peaks ( Figure 4 b). In the Ni 2p and Fe 2p spectra of the Ru / NiFe-LDH sample, the characteristic peaks of Ni 2p3 / 2 and Fe 2p3 / 2 are located at 855.49 eV and 712.00 eV ( Figure 4 c), belonging to Ni2+ and Fe3+ respectively. Comparing the XPS spectra of Ni and Fe before and after loading, it was found that the binding energy of Ni decreased by 0.11eV, and Fe also decreased by 0.12eV, which means that Ni and Fe obtained electrons after loading. Combined with EXAFS, it was further determined that electrons were transferred from Ru to Ni and Fe through the Ru-OM (M=Ni or Fe) bond, causing Ru to show positive charge. The high-resolution XPS spectra of LDH before and after Ru loading were compared. X-ray photoelectron spectroscopy (XPS) determined the chemical state and O doping state of Ru / NiFe-LDH. By comparing before and after loading, it was found that the peak at 463.31 in the Ru 3p spectrum was 3p3 / 2, the peak at 486.02 was Ru's 3p1 / 2, and the peak at 465.65 was Ru-O. A peak with a Ru-O bond was detected in the O 1s spectrum.
[0053] 3. Evaluation of PMS activation performance
[0054] The effect of Ru / NiFe-LDH on the performance of PMS was evaluated by the degradation of sulfamethoxazole (SMX). Figure 5As shown in a, under the conditions of lower catalyst (0.2g / L) and 0.5mMPMS content, the Ru / NiFe-LDH / PMS system almost completely degraded SMX within 30 minutes. The NiFe-LDH / PMS system and the Ru / NiFe-LDH* / PMS system were not completely degraded in 60 minutes. It can be seen that under the load conditions of Comparative Example 1, the catalytic performance of the prepared Ru / NiFe-LDH* is comparable to that of the pure NiFe-LDH, indicating that the Ru / NiFe-LDH with the Ru dosage in the embodiment of the present application has a catalytic removal effect on SMX. Using PMS alone for 60 minutes has a degradation efficiency of nearly 40%, which is attributed to the singlet oxygen produced by the self-degradation of PMS. When PMS is not present, the removal of SMX is completely due to the adsorption of the catalyst, and Ru / NiFe-LDH has almost no adsorption effect on SMX.
[0055] like Figure 5 As shown in Figure d, the catalysts with different Ru loadings were subjected to degradation experiments. The catalyst with low Ru loading in Comparative Example 1 had the same catalytic performance as the pure NiFe-LDH, which may be due to the lack of active sites leading to poor degradation performance. Figure 6 As shown in c, different PMS addition amounts were used. Although the addition amounts were different, the excellent degradation performance was still demonstrated. When the catalyst addition amount was changed, the performance was greatly affected. This is because the number of active sites increased. In order to save the amount of material while ensuring a good degradation effect, a catalyst content of 0.2 g / L was selected as an example in this application.
[0056] In the Ru / NiFe-LDH / PMS system, Figure 5 As shown in Figure e, the degradation efficiency is still good in the initial pH range of 3 to 11, which is related to the presence of high-valent metal active species in the system. It still shows very good degradation performance in a wide pH range (3-11), and the degradation performance is improved at a lower pH value of 3, because Ru (V) = O can exist more stably under acidic conditions; while in alkaline conditions (pH = 11), the degradation efficiency of the system is slightly inhibited, and the degradation efficiency of SMX drops from 100% to 92% within 30 minutes, which may be attributed to the mutual repulsion between ions caused by deprotonation under alkaline conditions. It shows that the Ru / NiFe-LDH composite material provided by the present invention is applicable to a wide pH range.
[0057] 4. Application in actual water bodies
[0058] The practical application value of Ru / NiFe-LDH / PMS is demonstrated by the degradation of SMX in actual water bodies, such as Figure 6As shown in a, SMX is degraded in different water matrices (tap water, Xiangjiang River water) with extremely high removal efficiency, indicating that the Ru / NiFe-LDH composite material provided in this application has good stability.
[0059] In order to further verify its universal applicability, ofloxacin (OFX), rhodamine B (RhB), methylene blue (MTB), tetracycline hydrochloride (TC), carbamazepine (CBZ), and bisphenol A (BPA) were selected for catalytic degradation. Figure 6 As shown in b, the removal efficiencies of OFX, RhB, MTB, TC, CBZ, and BPA reached 43%, 100%, 100%, 77%, 100%, and 35%, respectively, after 1 h, which indicates that Ru / NiFe-LDH is a promising heterogeneous catalyst. Considering the widespread distribution of inorganic anions and organic natural products in practice, e.g. Figure 6 As shown in Figure c, the presence of various anions in natural water bodies will change the acid-base conditions of the system and react with active substances. Under the condition of 10 mM anions, part of the degradation rate in the system was affected to a certain extent, and NO3-, SO42-, and H2PO4- had almost no effect. The addition of 10 mg / L humic acid (HA) caused a certain impact on the degradation efficiency of the Ru / NiFe-LDH / PMS system. It is reported that HA can interact with chemical substances during adsorption, catalytic reaction and oxidation to cause quenching. Another reason may be that HA will adsorb on the catalyst surface, compete with PMS or shield some active sites. The addition of Cl- ions has a promoting effect on the system. This is because Cl- may be oxidized to form an active substance with a higher potential, ClOH﹒-, which will promote degradation.
[0060] The suspension containing 50 mg of the catalyst was filtered onto a polyethersulfone (PES, pore size ~0.22 µm, diameter ~5 cm) membrane ( Figure 6 d, g), the planar SEM images show that Ru / NiFe-LDH is fully and evenly deposited on the surface of the PES membrane. The PES membrane has good adhesion and flexibility, providing sufficient adhesion area for Ru / NiFe-LDH. At the same time, the layered two-dimensional structure of Ru / NiFe-LDH provides abundant catalytic sites for activating PMS and degrading pollutants, such as Figure 6 h shows that during the continuous operation of 400 min, the constructed Ru / NiFe-LDH / PES / PMS system has excellent degradation performance and the degradation efficiency can reach 97%, which indicates that the Ru / NiFe-LDH / PES membrane system has high stability and the ability to treat pollutants in actual water bodies. In addition, during the operation, the water flux was maintained above 1300 L / m2 / h ( Figure 6i), indicating that the system has good water permeability.
[0061] The present application proposes a Ru / NiFe-LDH composite material, in which a single Ru atom is loaded on NiFe-LDH through the coordination of O atoms. The addition of Ru changes the electronic microenvironment of the coordination center and transfers electrons to Ni and Fe through the action of the O bridge, which improves the electron transport capacity of NiFe-LDH, thereby increasing the generation of singlet oxygen, and at the same time, optimizing the electronic structure to stabilize the Ru active site. The change of the coordination center and the electron transport cause Ru to be positively charged, so that the PMS anion is adsorbed near Ru, further forming a unique Ru (V) = O high-valent metal species. This application reports for the first time the role of high-valent species of precious metals in advanced oxidation in heterogeneous catalysis, which provides new insights into the application of advanced oxidation in the environment.
[0062] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Other modifications or equivalent substitutions made to the technical solution of the present invention by ordinary technicians in the field should be included in the scope of the claims of the present invention as long as they do not depart from the principle and scope of the technical solution of the present invention.
Claims
1. Application of Ru / NiFe-LDH composite material in activating PMS to degrade organic matter in water, characterized in that: The organic matter is any one or more of rhodamine B, methylene blue, carbamazepine or sulfamethoxazole. The preparation method of the Ru / NiFe-LDH composite material comprises the following steps: S1, uniformly mixing nickel salt, iron salt, urea, ammonium fluoride and water by ultrasonication, performing hydrothermal reaction, filtering, drying and grinding to obtain NiFe-LDH powder; S2. Dissolve RuCl3 in a beaker containing 85 ml ultrapure water and 10 ml 0.1 M NaOH; then add NiFe-LDH powder and stir at 50-60°C for 6-8 hours to obtain a dark green sample, which is then washed thoroughly with deionized water and dried. Among them, the mass ratio of RuCl3 to NiFe-LDH powder is 15~20:400~500; The content of Ru in the Ru / NiFe-LDH composite material is 1.5543wt% or 1.6621wt%; Wherein, the ratio of the nickel salt, the iron salt, the urea, the ammonium fluoride and the water is 3-4 mmol: 1-1.5 mmol: 120-130 mmol: 10-15 mmol: 80-90 ml.
2. The use according to claim 1, characterized in that: The ultrasonic time is 15-25 minutes; the hydrothermal reaction temperature is 110-120° C.; and the time is 10-12 hours.
3. The use according to claim 1, characterized in that: The amount of the Ru / NiFe-LDH composite material used in the degradation process is 0.18-0.2 g / L.
4. The use according to claim 1, characterized in that: The initial pH of the degradation process is 3-11.
5. The application according to claim 1, characterized in that it also includes: The Ru / NiFe-LDH composite material was deposited on the PES membrane.
Citation Information
Patent Citations
Monatomic ruthenium-loaded LDH (layered double hydroxide) catalyst as well as preparation method and application thereof in pathogenic bacterium killing
CN114917926A
Ruthenium-modified ferronickel layered double hydroxide catalytic material and preparation method thereof
CN116870929A